Study and Analysis of Some Real Life Applications of Exponential Function Based on Population Growth Rate of Nepal - Chaurasiya, Priyanshu; Sharma, Nimy; Chaudhary, Sanjana; Sah, Shilpy; Sahani, Suresh Kumar; Sahani, Kameshwar (Darul Yasin Al Sys, 2024)
This research investigates various real-world applications of exponential functions that are present in a country or region. Our goal was to gain an understanding of the exponential function. The exponential function is most commonly used in the growth and decay model. An introduction to the exponential function opens the project. We have got some real-world applications of the exponential function in this project, including: a. population growth: b. compound interest; c. bacterial proliferation; d. an increase in internet users; and so on. This work is motivated by the works of [1-13].